2022
DOI: 10.18865/ed.32.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Generation 1.5: Years in the United States and Other Factors Affecting Smoking Behaviors Among Asian Americans

Abstract: Introduction: Generation 1.5, immigrants who moved to a different country before adulthood, are hypothesized to have unique cognitive and behavioral patterns. We ex­amined the possible differences in cigarette smoking between Asian subpopulations who arrived in the United States at different life stages.Methods: Using the Asian subsample of the 2015 Tobacco Use Supplement to the Cur­rent Population Survey, we tested this Gen­eration 1.5 hypothesis with their smoking behavior. This dataset was chosen because it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Previous studies have shown that foreign-born nationals have lower odds of tobacco smoking [18][19][20][21][22]. This is similar to our findings that found 42% lower odds of tobacco smoking among foreign-born nationals compared to US-born nationals.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous studies have shown that foreign-born nationals have lower odds of tobacco smoking [18][19][20][21][22]. This is similar to our findings that found 42% lower odds of tobacco smoking among foreign-born nationals compared to US-born nationals.…”
Section: Discussionsupporting
confidence: 92%
“…In the study by Shi et al among Asian Americans, it was found that foreign-born males who migrated to the USA before age 12 had lower odds of smoking compared to those who migrated in adulthood. This pattern was found to be the opposite in foreign-born Asian females [ 20 ]. In a sample of Hispanic young adults in Florida, first-generation immigrants had a lower risk of tobacco and other substance use, which was explained as lower exposure to social stress than foreign-born naturals were exposed to [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation